Adapting Summer Education Programs for Navajo Students: Resilient Teamwork - Kahn, Carmella B.; Dreifuss, Heather; Teufel-Shone, Nicolette I.; Tutt, Marissa; McCue, Kelly; Wilson, Jamie; Waters, Amber-Rose; Belin, Kalvina L.; Bauer, Mark C. (Frontiers in Sociology, 2021)
In May 2020, the Navajo Native American Research Center for Health Partnership (Navajo NARCH) was scheduled to launch two summer programs: a 10 week-long Summer Research Enhancement Program (SREP) for undergraduate students to learn and practice health research methods and participate in a practicum experience, and a week-long Indigenous Summer Enhancement Program (ISEP) for high school students that introduces a range of health professions and develops leadership qualities. Students accepted into the programs are predominantly Navajo and live within Navajo Nation (NN) during the summer. Due to NN restrictions and CDC guidelines for physically distancing in response to the coronavirus (COVID-19) pandemic, the Navajo NARCH team organized to offer both programs entirely online via Zoom™. This paper explores the instructional teams’ adaptation process to maintain a commitment to preserve the programs’ supportive environment for exploring and developing strong multicultural approaches in public health and health research. In preparation for online instruction, the team developed and offered workshops for staff and instructors to address anticipated challenges. The team identified the following challenges: technological difficulties, social disconnectedness, consistent student engagement, and facilitation of a practicum research experience. Results showed that program adaptations were successful as the team applied collaborative and holistic approaches, and established social connections remotely with students to offer meaningful research and practicum experiences.